Why should security aspects be more seriously considered in development of Serbian tourism industry? - Radović Vesela; Arabska Ekaterina (University Educons, Faculty of Sports and Tourism, Novi Sad, 2016)
Tourism today is becoming a part of everyday life for millions of people all over the world. According to the Travel&Tourism Competitiveness Report 2013, security is among the critical factors determining the competitiveness of a country's tourism industry. The most common reasons that are usually given are growing threats from terrorist acts, relatively high level of crime in the region and unknown diseases. The World Tourism Organization stated that one of the factors limiting the development of the industry is that issues related to security in tourism are not sufficiently regulated. The statistics show that the vast majority of organizations in tourism infrastructure are operating at a loss due to terrorism and natural disasters. This statement was particularly confirmed after a great decrease of tourist visits to Phuket and New Orleans after the horrible natural disasters (tsunami and hurricane Katrina, respectively). The question which arises in scientific and public community is: ''How to provide an adequate level of security for tourists.'' Tourism is announced as one of the priorities in future development of the Republic of Serbia. The author used the methodology appropriate for social science. The study results have indicated an urgent need for acceptance of a holistic approach to the issue. Tourism industry has to recognize the importance of security in its daily activities and in these efforts needs to closely cooperate with security services on the local and national level.